Effect of incremental static damage on modal frequencies of reinforced concrete beams - Ibrahim, Zainah; Hanif, Muhammad Usman; Xin Lim, Huan; Xian Hang, You (International Journal of Integrated Engineering, 2018)
The modelling and the failure mechanisms of RC structures is a complex phenomenon because the constituent materials’ strengths are combined to overcome their weaknesses. Therefore, the failure mechanisms have not been understood completely. Modelling concrete beams using plasticity approaches has gained a lot of attention because of its versatility. This research incorporates the plasticity model with continuum damage model to evaluate the modal frequency deterioration of the reinforced beams. These beams were incrementally damaged in flexure using finite element modelling. It was observed that the model represents the damage mechanism of RC beams quite reasonably. The dynamic response of the beams is also in line with the experimental results. Based on the dynamic response, it was observed that the modal frequencies are sensitive to damage at initial stages and there is not significant reduction in the natural frequencies at complete damage.